2012
DOI: 10.1002/sres.2140
|View full text |Cite
|
Sign up to set email alerts
|

Designing Sustainable Food Security Policies in Sub‐Saharan African Countries: How Social Dynamics Over‐Ride Utility Evaluations for Good and Bad

Abstract: Sub-Saharan African economies depend heavily on agriculture. Seed from improved varieties and other inputs are imperative to the transformation of the agricultural sector from subsistence farming to small-scale commercial agriculture and thus to increasing food security on the continent. Farmers make the decision to adopt seed from improved varieties based on a number of seed attributes. These range from tangible attributes such as input costs and yield to intangible attributes such as trust in seed from impro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 27 publications
1
19
0
1
Order By: Relevance
“…Rational action models may be useful for simulating biophysical system outputs. However, they are not appropriate in accounting for the diverse rationalities that different types of decisionmakers employ in real life, as several studies in the social sciences have shown (Krandikar and Risbey, 2000;Jager et al, 2000;Darnhofer et al, 2010;Kaine and Cowan, 2011;Bacon et al, 2012;Kopainsky et al;Rasmussen and Reenberg, 2012;Ceddia et al, 2013;Galt, 2013). When translated into policy, such simplified models tend to result in a 'technical-fix' approach (Krandilkar and Risbey, 2000;Giddings et al 2002;Ribeiro and Shand, 2008;Galt, 2013;Home et al, 2014).…”
Section: Decision-making Modelmentioning
confidence: 99%
“…Rational action models may be useful for simulating biophysical system outputs. However, they are not appropriate in accounting for the diverse rationalities that different types of decisionmakers employ in real life, as several studies in the social sciences have shown (Krandikar and Risbey, 2000;Jager et al, 2000;Darnhofer et al, 2010;Kaine and Cowan, 2011;Bacon et al, 2012;Kopainsky et al;Rasmussen and Reenberg, 2012;Ceddia et al, 2013;Galt, 2013). When translated into policy, such simplified models tend to result in a 'technical-fix' approach (Krandilkar and Risbey, 2000;Giddings et al 2002;Ribeiro and Shand, 2008;Galt, 2013;Home et al, 2014).…”
Section: Decision-making Modelmentioning
confidence: 99%
“…Furthermore, it can provide a good information exchange, which is also an important trigger for the adoption of disruptive process innovations [67,78,83,97,99,101,102]. To push a new production technology, farmers need to have access to a market where they can buy the technology or the knowledge about this specific technology and where they can get a credit for this particular purchase.…”
Section: Drivers For Disruptive Process Innovationsmentioning
confidence: 99%
“…Con una perspectiva dinámica, Kopainsky et al 25 desarrollan un marco socio-técnico de análisis de políticas públicas, que tiene por objeto mejorar la comprensión de la transformación de la agricultura de subsistencia y evaluar las políticas de apoyo a esta transformación. Usando un modelo de simulación adoptan determinantes y procesos descritos en la literatura, confirmados por análisis empíricos; cuyos determinantes más importantes son la utilidad local de semillas, la compatibilidad con las prácticas agrícolas de subsistencia y las habilidades para el cultivo, entre otros.…”
Section: Según La Fao "Existe Seguridad Alimentaria Cuando Todas Lasunclassified